Multipoint pacing improves peripheral hemodynamic response: Noninvasive assessment using radial artery tonometry. Issue 2 (8th January 2018) - Ciconte, Giuseppe; Ćalović, Žarko; Vicedomini, Gabriele; Cuko, Amarild; McSpadden, Luke C.; Jiang, Chunlan; Ryu, Kyungmoo; Caporaso, Igor; Stutz, Robert; Winter, Dean; Saviano, Massimo; Vitale, Raffaele; et al.
Abstract: Background: Multipoint left ventricular (LV) pacing (MultiPoint™ Pacing [MPP], Abbott, Sylmar, CA, USA) improves the response rate to cardiac resynchronization therapy (CRT). We evaluated the feasibility of noninvasive radial artery tonometry (RAT) to characterize arterial pressure morphology changes (pre‐ejection period [PEP] and ejection duration [ED]) between conventional CRT and MPP pacing interventions. Methods: Patients with a MPP‐enabled CRT device (Quadra Assura MP™, Abbott) underwent noninvasive RAT assessment (SphygmoCor CVMS, AtCor Medical Inc., Itasca, IL, USA) at 3–6 months after implantation. A pacing protocol was performed in a randomized order including one optimized conventional biventricular CRT (CONV) configuration using the distal electrode and five MPP configurations. The PEP, ED, and PEP/ED ratio were determined for each intervention from the RAT pressure waveform and electrocardiogram. Results: Pressure waveforms were successfully recorded in 19 patients (89% male, QRS 147 ± 16 ms, 63% ischemic). In 17/19 (89%) patients, at least one MPP intervention resulted in improved PEP, ED, and PEP/ED compared to CONV. The MPP intervention with greatest separation of LV cathodes and minimum intra‐LV delay significantly improved PEP (mean PEP –15 ± 33% vs –8 ± 32% [CONV], P = 0.04) and ED (mean ED +8 ± 8% [MPP] vs +4 ± 7% [CONV], P = 0.02), and PEP/ED (–0.07 ± 0.14 [MPP] vs –0.04 ± 0.13 [CONV], P = 0.02) compared with CONV. Conclusions: Noninvasive RAT efficiently characterizes changes in PEP and ED between CONV and MPP interventions. MPP configurations using the widest separation among LV cathodes and minimum intra‐LV delay may significantly improve RAT‐derived parameters as compared to conventional CRT.